EFFECTIVENESS OF DEVELOPMENT ANDRA’S NURSING INFORMATIC SYSTEM APPLICATION (ANNISA) TOWARDS NURSING DOCUMENTATION COMPLETENESS - Candra Saputra; Yulastri Arif; Fitra Yeni (LLDIKTI Wilayah X, 2020)
Nurses have an important role in improving the completeness of nursing documentation. Increasing the completeness of nursing documentation can be done through changing paper-based documentation to electronic-based with the development of ANNISA applications. The ANNISA application developed is oriented to NNN Linkage nomenclature. The purpose of this study was to determine the effectiveness of ANNISA development on the completeness of nursing documentation. This study conducted using a quantitative research with a quasy experimental design and a Time Series Non Equevalent Control Group Design approach. The sampling technique used was proportional random sampling with a total sample of 96 nurses in health center Pekanbaru City. The results showed that there were differences in the measurement Completeness of nursing documentation between pretest and postest measurement in the intervention group (p Value = 0,000 <α = 0.05) and there were differences in completeness of nursing documentation between the intervention group and the control group in the pretest, postest-1 and postest-2 measurement (p Value = 0,000 <α = 0.05). there was an increase in differences Completeness of nursing documentation from pretest , posttest-1 and postest-2 measurements after ANNISA model development in the intervention group and the control group (p Value = 0,000 <α = 0.05). It is expected that the health center can use the ANNISA application as an alternative in solving the problem of completing nursing documentation carried out by nurses in the Health Center Pekanbaru City